How Low-Carbon Heat Requirements for Direct Air Capture of CO2 Can Enable the Expansion of Firm Low-Carbon Electricity Generation Resources - Slesinski, Daniel; Litzelman, Scott (Frontiers in Climate, 2021)
A rapid build-out of direct air capture (DAC), due to worsening climate-change effects, will require significant amounts of both low-carbon thermal and electrical energy. Firm low-carbon power resources, including nuclear, geothermal, or natural gas with carbon capture, which also will become more highly valued as variable renewable energy penetration increases, would be able to provide both heat and electricity for DAC. In this study, we examined the techno-economic synergy between a hypothetical DAC plant in the year 2030 and a nuclear small modular reactor, and determined two avenues for which this relationship could benefit the nuclear plant. First, we demonstrated that, under certain assumptions, selling a portion of its energy to a DAC facility allows the nuclear plant to take in 27% less revenue from selling electricity to wholesale markets than its projected levelized cost, and still break even. Second, after estimating a potential revenue stream, we showed that an integration with DAC allows for the nuclear plant’s capital costs to be up to 43% higher than what would be required if only selling electricity to wholesale markets. This could enable the nuclear plant to operate economically even in the face of variable and decreasing wholesale electricity prices, and also could offer developers more financial certainty when planning a new project. Ultimately, this study shows that the need for low-carbon energy for DAC plants might incentivize the development of advanced nuclear plants and firm low-carbon resources more broadly.